Incidence and Risk factors of Intraoperative Hyperglycemia in Non-diabetic Patients: A Prospective Observational Study - Regmi, Gunjan; Khanal, Kanak; Arjyal, Batsalya; Pyakurel, Kumud; Shahi, Rejina; Bohara, Chetan (Birat Journal of Health Sciences, 2024)
Introduction: Intraoperative hyperglycemia is recognized as a significant concern, being associated with various complications such as surgical site infection, cardiovascular events, kidney injury, stroke, and even death. These complications can occur in both diabetic and non-diabetic patients. However, previous studies have not fully established the incidence and risk factors of intraoperative hyperglycemia in non-diabetic patients. Objectives: The primary objective was to find the incidence of intraoperative hyperglycemia in non-diabetic patients. The independent risk factors for intraoperative hyperglycemia and the incidence of surgical site infection in patients with intraoperative hyperglycemia were the secondary outcome. Methodology: A quantitative prospective observational study was performed after IRC approval. Six hundred five non-diabetic patients above 18 years who underwent intermediate- to high-risk surgery were included in the study. For 18 months capillary blood glucose levels were measured in all patients during surgery. Risk factors and postoperative surgical site infection was noted to identify relation and risk factors of intraoperative hyperglycemia. Results: Seventy-eight (12.9%) patients developed hyperglycemia during surgery. The independent risk factors for intraoperative hyperglycemia were an ASA status ≥3, preoperative impaired fasting blood sugar (OR 20.27, 95%CI:10.19–37.63, p<0.001, intraoperative hypotension (OR 4.6, 95%CI: 2.36–8.97, p < 0.001), intraoperative blood transfusion (OR 4.45, 95%CI: 1.88–10.56, p < 0.001) and steroid use (OR 2.81, 95%CI: 1.38–5.73, p = 0.003). Surgical site infection was higher in patients with intraoperative hyperglycemia compared with patients without intraoperative hyperglycemia (5 [6.8%] vs. 9 [1.7%], respectively, p = 0.010). Conclusion: Intraoperative hyperglycemia was observed among non-diabetic patients undergoing intermediate- to high-risk surgeries. Patients with risk factors for intraoperative hyperglycemia should undergo close monitoring of their blood glucose levels.